Evaluation of a textual exercise in the 6th grade Turkish course workbook in terms of textuality - (:unkn) unknown (ELSEVIER SCIENCE BV, 2013)
To understand a text, it is necessary to support a text with some exercises. The main focus of our study is the relationship between the textuality and textual exercises in the 6th Grade Turkish Course Workbook. For this purpose, in this study firstly, it has been analysed that which exercises are used in workbook to consolidate a text in the 6th Grade Turkish Course Course book and which skills are related to these exercises. Afterwards, by identifying the standard of textuality corresponding to the activity of skill area, suggestions have been made in this direction. (C) 2012 Published by Elsevier Ltd.
Keywords: Turkish Course; workbook; textuality; textual exercise; skills